Patients’ experiences in early satiety after total gastrectomy for gastric cancer: a phenomenological study - Salvatore Vaccaro; Matías Eduardo Díaz Crescitelli; Stefano Mastrangelo; Nadia Fornaciari; Elisabetta Reverberi; Silvia Di Leo; Luca Ghirotto (Frontiers in Nutrition)
IntroductionThis study examines how gastric cancer patients adjust their eating habits and quality of life after total gastrectomy, particularly concerning early satiety. While total gastrectomy may provide a potential cure, it also leads to significant physical, psychological, and social changes. Understanding these adaptations is essential for enhancing survivorship care.MethodsWe conducted a qualitative study utilizing a phenomenological approach to gain insights into the lived experiences of gastric cancer patients following total gastrectomy. Semi-structured interviews were analyzed to identify key themes related to eating habits and quality of life.ResultsFour core themes emerged: (1) Ineluctability of bodily transformations—patients experienced significant disruptions to their bodily identity; (2) Feelings of weaning and loss of habits—a sense of mourning for lost routines and pleasures; (3) Redefining habits—the process of adapting to new eating patterns; and (4) Experiencing tentative conviviality—struggles to restore social interactions around meals. Social anxiety, particularly regarding dining outside the home, was a notable challenge. Family caregivers played complex roles, providing both support and unintentional obstacles.DiscussionThe findings highlight the multifaceted impact of total gastrectomy on patients’ lives, influencing their physical health, psychological well-being, and social dynamics. Survivorship care plans should consider these aspects to facilitate adaptation. Targeted interventions, such as nutritional counseling, telemonitoring, and digital tools, are suggested to assist patients in adjusting to post-gastrectomy life. These strategies could enhance quality of life and promote improved physical, psychological, and social well-being integration.